Warthin's tumor: An unknown pathogenesis: A neoplasm or a reactive hyperplasia? - Arpaci Bozdogan Rabia; Linke Serınsoz Ebru; Kara Tuba; Gursoy Didar; Orekici Gulhan; Ozcan Cengiz (Wolters Kluwer Medknow Publications, 2015)
Background and Aims: To examine the probable role of angiogenesis and lymphangiogenesis in the pathogenesis of Warthin's tumor. Materials and Methods: Sixty-one patients with Warthin's tumor (n = 40), branchial cysts (n = 6), thymic cysts (n = 3), or tonsillar lymphoepithelial cysts (n = 12) were included. Forty Warthin's tumors were used as the lesion group, and 21 lymphoepithelial cysts were used as a control group. 29 lymph nodes around the Warthin's tumor, four of which showed salivary duct inclusions, were also evaluated. Blood vessel density was defined as an indicator of angiogenesis by examining CD31 and FVIII Ag expression, and lymphatic vascular density was defined as an indicator of lymphangiogenesis by evaluating LYVE-1 and podoplanin expression by immunohistochemical analysis. Statistical Analysis Used: Data are expressed with descriptive statistics. Comparative analysis was performed using Shapiro-Wilks, Mann-Whitney U, and Kruskal-Wallis tests. A P < 0.005 was considered to indicate statistical significance. Statistical analysis was performed using the MedCalc ® v.10.3.0 software. Results: The lesion group had higher mean values of age (58 vs. 11 years, P = 0.001), smoking rate (92.3% vs. 19%, P < 0.001), stromal degeneration (100% vs. 42.9%, P < 0.001), lymph node involvement around the lesion (87.9% vs. 12.1%, P < 0.001), salivary duct inclusion (25% vs. 0%, P = 0.0001), than those of lymphoepithelial cysts. Blood vessel density (51.92 ± 25.64 vs. 8 ± 5.35, number/5 high power fields (HPF), P < 0.001) and lymphatic vascular density (68.95 ± 21.32 vs. 21.10 ± 4.05 number/5 HPF, P < 0.001) were higher in Warthin's tumors than lymphoepithelial cysts. Warthin's tumors, and lymph nodes with inclusions had similar levels of blood and lymphatic vascular density, which was higher than those of lymph nodes (P < 0.0001). Conclusions: Warthin's tumor is a true neoplastic epithelial proliferation associated with increased angiogenesis and lymphangiogenesis and induces reactive lymph node hyperplasia.